Legal Reconstruction of Customer Protection in Islamic Banking from the Perspective of Statutory Regulations and Sharia Principles: REKONTRUKSI HUKUM PERLINDUNGAN NASABAH PERBANGKAN SYARIAH DALAM PERSPEKTIF PERATURAN PERUNDANG UNDANGAN DAN PRINSIP SYARIAH - Wahyuni, Nur; Melani, Elmi Ayu; Yunus, Muhaimin; Ilham (Ekonomipedia: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
Abstract. Islamic banking in Indonesia, while integral to the financial system, still faces challenges in customer protection related to regulations and the implementation of sharia principles. This research aims to reconstruct the legal framework for customer protection by analyzing the alignment between national regulations and sharia principles. The findings indicate a need for better integration between national law and maqashid sharia, including improvements in dispute resolution mechanisms, transparency of contracts, and strengthening oversight by the Sharia Supervisory Board. The goal is to create a more just and sustainable protection system for customers of Islamic banking. Abstrak. perbankan syariah di Indonesia, meskipun integral dalam sistem keuangan, masih menghadapi tantangan dalam perlindungan nasabah terkait regulasi dan implementasi prinsip syariah. Penelitian ini bertujuan untuk merekonstruksi kerangka hukum perlindungan nasabah dengan menganalisis kesesuaian peraturan nasional dan prinsip syariah. Hasilnya menunjukkan perlunya integrasi yang lebih baik antara hukum nasional dan maqashid syariah, termasuk perbaikan mekanisme penyelesaian sengketa, transparansi akad, dan penguatan pengawasan oleh Dewan Pengawas Syariah. Tujuannya adalah menciptakan sistem perlindungan yang lebih adil dan berkelanjutan bagi nasabah perbankan syariah.